2020
DOI: 10.1167/tvst.9.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Challenges of Deep Learning in Optical Coherence Tomography for Retinal Diseases: A Review

Abstract: Artificial intelligence (AI)-based automated classification and segmentation of optical coherence tomography (OCT) features have become increasingly popular. However, its 3-dimensional volumetric nature has made developing an algorithm that generalizes across all patient populations and OCT devices challenging. Several recent studies have reported high diagnostic performances of AI models; however, significant methodological challenges still exist in applying these models in real-world clinical practice. Lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 63 publications
0
42
0
1
Order By: Relevance
“…A recent study emphasized the large amount of OCT data required to train a DL model but did not investigate the feasibility of FSL in OCT imaging [ 40 ]. To address the limitations of traditional DL models, we first performed an experiment to explore the feasibility of FSL in the OCT imaging domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study emphasized the large amount of OCT data required to train a DL model but did not investigate the feasibility of FSL in OCT imaging [ 40 ]. To address the limitations of traditional DL models, we first performed an experiment to explore the feasibility of FSL in the OCT imaging domain.…”
Section: Discussionmentioning
confidence: 99%
“…The low resolution may affect the classification results of the DL model [ 53 ]. Second, this study does not include a volumetric analysis for OCT. A recent study demonstrated that there is a lack of standardization in the OCT acquisition and analysis protocol [ 40 ]. Future studies should consider the variations in OCT images and devices.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of large image datasets from multiple OCT devices, non-standardized imaging or postprocessing protocols between devices, limited graphics processing unit capabilities for exploiting 3D features, and inconsistency in the reporting metrics are major hurdles in enabling AI for OCT analyses. 320,321 Furthermore, machine learning and AI for health must be reproducible to ensure reliable clinical use. Recent evaluations found that machine learning for health fared poorly compared with other areas regarding reproducibility metrics, such as dataset and code accessibility.…”
Section: Oct and Deep Learning Neural Network And Artificial Intelligencementioning
confidence: 99%
“…The application of deep learning methods to OCT medical images is a recent trend and only few examples of application are available. Ophthalmology being the oldest context of application of OCT, most examples are found in this area, and some others in cardiology and breast cancer [42][43][44][45]. In gastroenterology of the lower track (colon), only one recent work has been identified [46].…”
Section: Introductionmentioning
confidence: 99%